The Human Need for Truth as Hope for a Broken World in the Reflection of Gabriel Marcel - Januszewski, Zbigniew (Filozofia Chrześcijańska, 2012)
Gabriel Marcel is known as a Christian existentialist and a philosopher of hope. Hope for human beings in the broken world is the main thesis of the article. Marcel introduced the idea of a broken world to philosophy as a negative in the moral sense, multidimensional notion that is di- rectly related to our human world. According to Marcel, the root of the broken world is the mys- tery of evil. The broken world occurs everywhere where a human being is left alone without an authentic community, without brotherhood, without hope. However, even in the broken world there is hope for us. In the human soul Marcel discovered a mysterious sensitivity to the light of the truth and the deepest need for the truth. Those qualities of the human heart prove that it is possible for us to turn away from the broken world and to turn to the spirit of truth.